Civil liability and financial security for offshore oil and gas activities - Faure, Michael G. 1958- (Cambridge University Press, 2017)
"Civil Liability and Financial Security for Offshore Oil and Gas Activities provides insights into the liability and compensation regime for offshore- related damage. The book analyses the legal regime in a variety of states (including the US and the UK) as well as the EU regime. In addition the various compensation mechanisms and amounts available today to compensate offshore-related damage are described and critically analysed. Moreover, based on in-depth interviews with a wide variety of relevant stakeholders including insurers, representatives from supervisory authorities, and oil and gas producer. This volume also provides a variety of policy recommendations, formulated to provide an optimal compensation regime for offshore-related damage"...
Keywords: LAW / Civil Law; Recht; Liability for oil pollution damages; Oil pollution of the sea -- Law and legislation; Offshore oil well drilling -- Law and legislation; Offshore gas well drilling -- Law and legislation; Oil and gas leases; Liability (Law); Compensation (Law)